(untitled) (Journal of Atomic and Molecular Sciences, 2012)
A simple scheme for transferring an unknown atomic state based on the pairing of off-resonant Raman transitions is proposed. The scheme is insensitive to the atomic spontaneous emission, cavity decay, and fiber decay. Meanwhile, in the scheme, operations between any pair of atomic qubits and selective parallel two-qubit operations on different qubit pairs can be implemented. The atoms, the cavity modes and the fiber are not excited during the operations. A quantum communication network for transferring quantum information can be established. Therefore the scheme would be a useful step toward future scalable quantum computing networks.